High temperature phases in the 0.98PbZrO30.02Pb(Ni1/3Nb2/3)O3 ceramic - W. Qu; X. Tan; N. Vittayakorn; S. Wirunchit; M. F. Besser (My University, 2009)
The phase evolution with temperature in the 0.98PbZrO3–0.02Pb(Ni1/3Nb2/3)O3 ceramic was investigated with dielectric permittivity and polarization measurements, hot stage transmission electron microscopy, and high temperature x-ray diffraction. Below 190 °C, the ceramic is in the antiferroelectric phase with characteristic 14{110}c superlattice diffractions. In this stage, typical antiferroelectric 180° domains were observed. Between 190 and 220 °C, an intermediate phase, which is characterized by 12{110}c-type superlattice diffractions, was detected. Evidences are found to suggest that this intermediate phase is ferroelectric. The 12{110}c-type superlattice diffraction persists even into the paraelectric phase above 220 °C. In addition, there exists an incommensurate phase between the low temperature antiferroelectric phase and the intermediate ferroelectric phase.
Keywords: Antiferroelectricity; Ferroelectric ceramics; Ferroelectric and Piezoelectric Materials